Teaching Activities in An EFL Class for Refugees at Immigration Detention Center In Balikpapan-Indonesia - Rorenta Tobing (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2022)
This research was designed to study teaching activities for speaking in an EFL refugee class at Immigration Detention Center in Balikpapan. The purpose of this study was to investigate the speaking activities that the teacher conducted, as well as how the teacher worked those activities and the challenges that appeared when the teacher performed teaching activities for teaching speaking. The research was done in Immigration Detention Centre, Lamaru, Balikpapan, in December 2019. The research sample in this study was one teacher of an EFL class of refugees in IDC Balikpapan. The study was based on qualitative case study research. Data were collected by using two instruments, classroom observation, and interview. The result indicated that various activities were conducted by the English teacher for teaching speaking in this class. It showed that the teacher taught ten exercises: discussion, roleplay, brainstorming, storytelling, interview, picture describing, game, presentation, field trip, and cooking activity. The teacher used the real-life situation as the topics for speaking activities in EFL class, applied pair or group learning, motivated the learners, used students centered method to encourage learners to be free to talk, and made only principal corrections when the learners were doing speaking activities. The challenges that the teacher faced while applying speaking activities in this EFL class learning process include language barriers, different educational backgrounds and life experiences, the psychological condition of the learners, and uncomfortable classroom situations. A professional teacher's certificate and training must be needed for teaching EFL refugee classes. So, it is necessary to create a particular course or class for learning to teach EFL classes for refugees in the English Education programs. EFL teacher of refugees is not only teaching language. The teacher is a facilitator, a guide, and a motivator to the EFL learners.